Situation Report: Baltic Area, 4 December 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Leading Personnel Changes since Gorbachev's Assumption of Power Dissident Pastor Allegedly Recants / by Toomas Ilves New Developments in Russification Policy in Cultural Center / by Toomas Ilves Recent Government Changes / by Dzintra Bungs Leading Personnel Changes since Gorbachev's Assumption of Power / by Dzintra Bungs Cultural Nationalism / by Saulius Girnius New President and Premier / by Saulius Girnius Leading Personnel Changes since Gorbachev's Assumption of Power / by Saulius Girnius Apparent Criticism of Lithuania by Central Soviet Authorities / by Saulius Girnius